The Language of Lies: A Content Analytic Approach. (September 2014) - Driskell, T.; Neuberger, L.; Driskell, J. E.; Burke, C. S.; Salas, E.
Past research on deception detection has demonstrated the diagnostic value of attending to verbal content (e.g., message content) over nonverbal cues (e.g., gaze aversion; Vrij, 2008). Moreover, research has also demonstrated the value of computer-based text analysis programs for distinguishing truthful from deceptive communications (Hauch, Masip, Blandon-Gitlin, & Sporer, 2012). The aim of this research is to add to the corpus of studies examining linguistic features of deceptive communications by comparing existing linguistic models (e.g., Newman, Pennebaker, Berry, & Richards, 2003) to our own approach. Based on our model, the results demonstrated that lies contain more affective words, are less detailed, and are more uncertain. Implications are discussed.